A Visual Semiotic Analysis on the Spongebob Movie - Junika Sihite; Muhizar Muchtar; Rahmadsyah Rangkuti (LingPoet: Journal of Linguistics and Literary Research, 2021)
Visual Semiotics is a new semiotic branch that analyzes how visual signs or visual images convey messages. In visual semiotic, a sign can be a word, sound, or visual image. Spongebob Movie is one of category of visual semiotic. It consists of picture and subtitle on it. By using visual semiotic analysis, this research aimed to identify the sign found in the Spongebob movie: Sponge Out of Water and how it is interpreted. The Spongebob Movie: Sponge Out of Water as the data of the research are collected by using qualitative audio and visual materials from Spongebob.fandom.com as the source of the data. It is twenty nine data analyzed by using visual semiotic with the theory proposed by Charles Sanders Pierce. This research uses qualitative data analysis as the method of the study. Each data of the research consists of the sign and meaning. The signs was identified based on Charles Sanders Pierce triadic sign (Representament, Objet, and Interpretant) and there are three steps in interpreting the sign namely, non-verbal communication legisign, framing techniques and communicative act.